Tháng Năm 19, 2024

\(B = \left( {\frac{1}{{\sqrt a – 2}} + \frac{1}{{\sqrt a + 2}}} \right).\frac{{a – 4}}{{\sqrt a }}\) với \(a > 0,\,a \ne 4\) A \(B = \frac{{\sqrt a }}{{\sqrt a + 2}}\) B \(B = \frac{1}{{a – 4}}\) C \(B = 1\) D \(B = 2\)

\(B = \left( {\frac{1}{{\sqrt a – 2}} + \frac{1}{{\sqrt a + 2}}} \right).\frac{{a – 4}}{{\sqrt a }}\) với \(a > 0,\,a \ne 4\)

A \(B = \frac{{\sqrt a }}{{\sqrt a + 2}}\)

B \(B = \frac{1}{{a – 4}}\)

C \(B = 1\)

D \(B = 2\)

Hướng dẫn Chọn đáp án là: D

Phương pháp giải:

Sử dụng công thức: \(\sqrt {{A^2}B} = \left| A \right|\sqrt B = \left\{ \begin{array}{l}A\sqrt B \,\,\,khi\,\,A \ge 0\\ – A\sqrt B \,\,\,khi\,\,\,\,A < 0\end{array} \right..\)

Lời giải chi tiết:

Với \(a > 0,\,\,a \ne 4\) ta có:

\(\begin{array}{l}B = \left( {\frac{1}{{\sqrt a – 2}} + \frac{1}{{\sqrt a + 2}}} \right).\frac{{a – 4}}{{\sqrt a }} = \left( {\frac{{\sqrt a + 2}}{{a – 4}} + \frac{{\sqrt a – 2}}{{a – 4}}} \right).\frac{{a – 4}}{{\sqrt a }}\\\,\,\,\, = \frac{{2\sqrt a }}{{a – 4}}.\frac{{a – 4}}{{\sqrt a }} = 2.\end{array}\)

Vậy \(B = 2\).

Chọn D.